MITIGATIVE EFFECTS OF Moringa Oleifera ON PROGESTERONE LEVEL OF FEMALE WISTAR RAT EXPOSED TO PETROLEUM PRODUCTS (FUDMA JOURNAL OF SCIENCES, 2025)
Petroleum products are mixtures of complex compounds or materials derived from crude oil, the majority of petroleum is converted to petroleum products, which include several classes of fuels. Such as petrol, diesel, kerosene, heavy gas oil and many others and its by-products contribute to air pollution and global warming. Twenty (21) rats were randomly divided into seven groups of three rats each. Group A were administered with petrol only. Group B were administered with petrol and later treated with Moringa oleifera, Group C were administered with diesel only. Group D were administered with diesel and later treated with Moringa oleifera, Group E were administered with kerosene only. Group F were administered with kerosene and later treated with Moringa oleifera. Group G were administered with Moringa oleifera extract only and served as control group. A cannula attached to the 5 millilitres syringe was used in administration of the aqueous Moringa oleifera extract at the dose rate of 40mg/kg/rat while the rats were properly restraint using scrubbing method. Blood was collected through cardiac puncture and analyzed. The results showed exposure to petrol, diesel and kerosene decrease serum progesterone level in rats (p < 0.05). Treatment with Moringa oleifera effectively reversed this decline and normalized progesterone concentrations to control levels.
Keywords: Progesterone; Moringa oleifera; Petroleum Products; Wistar Rats